2016
DOI: 10.1523/jneurosci.2265-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Relevance of Cortical Neural Ensemble Responses Emerges Suddenly

Abstract: Whereas many laboratory-studied decisions involve a highly trained animal identifying an ambiguous stimulus, many naturalistic decisions do not. Consumption decisions, for instance, involve determining whether to eject or consume an already identified stimulus in the mouth and are decisions that can be made without training. By standard analyses, rodent cortical single-neuron taste responses come to predict such consumption decisions across the 500 ms preceding the consumption or rejection itself; decision-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
164
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(184 citation statements)
references
References 85 publications
18
164
2
Order By: Relevance
“…Hidden Markov models of multiple simultaneously recorded in vivo spike trains have revealed transitions between relatively stable discrete activity states in premotor and prefrontal cortex of monkey performing a spatial short-term memory task [17,25,26] or freely viewing a scene [27], and in gustatory cortex of rats processing tastants [28]. The timing of such state transitions both correlates with ongoing behavior [27,29] and is predictive of an ensuing response [30]. …”
Section: Evidence For Multiple Attractor States and Itinerancymentioning
confidence: 99%
See 1 more Smart Citation
“…Hidden Markov models of multiple simultaneously recorded in vivo spike trains have revealed transitions between relatively stable discrete activity states in premotor and prefrontal cortex of monkey performing a spatial short-term memory task [17,25,26] or freely viewing a scene [27], and in gustatory cortex of rats processing tastants [28]. The timing of such state transitions both correlates with ongoing behavior [27,29] and is predictive of an ensuing response [30]. …”
Section: Evidence For Multiple Attractor States and Itinerancymentioning
confidence: 99%
“…Evidence for a delayed rapid transition from one discrete attractor state to another during decision making has been accrued during taste processing (where the decision is to expel or ingest a tastant) [28,30], in a somatosensory task [80], and in a detection of motion direction task [32]. However, an alternative analysis of the latter task revealed ramping as the typical dynamics during stimulus acquisition, with rapid transitions corresponding only to changes of mind [81].…”
Section: Computational Models With Attractor-state Itinerancymentioning
confidence: 99%
“…In contrast, a good deal of coherent progress has been made toward characterizing primary gustatory cortical (GC) taste responses in awake rats, mainly (but not ubiquitously) using electrophysiology. This work has exposed reliable properties of taste spiking activity in relation to behavior, specifically revealing: 1) that single-neuron taste responses vary widely in breadth, with responses to multiple tastes appearing in the same region, and even within the same single neurons (Katz et al, 2001;Fontanini & Katz, 2006;Accolla et al, 2007;Samuelsen et al, 2013); 2) that these responses progress through a series of firing-rate "epochs," coding in turn the presence, physical properties, and palatability of a taste across 1-1.5s (Katz et al, 2001;Bahar et al, 2004;Sadacca et al, 2012;Maier & Katz, 2013;Samuelsen et al, 2013); 3) that the late-epoch palatabilityrelated firing is uniquely affected by experience-driven shifts of taste palatability (Bahar et al, 2004;Fontanini & Katz, 2006;Grossman et al, 2008;Moran and Katz., 2014); and 4) that in single trials the onset of palatability is a sudden, coherent network phenomenon, the timing of which predicts and impacts behavior (Jones et al, 2007;Sadacca et al, 2016;Li et al, 2016). A test of whether mouse GC neurons respond in a like manner has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The description of sudden transitions between states lead to the suggestion that a stochastic, jumping model of decision making could account for ingestive decisions more accurately than the traditional diffusion-to-bound model, particularly in conditions of noisy signals [29,30] (Figure 1). Recent data confirmed this suggestion in both GC [31] and lateral intraparietal area (LIP) [32]. Finally, recent work unveiled that metastability is not limited to evoked activity, but can also be observed during spontaneously ongoing activity [28] (Figure 1d).…”
Section: Introductionmentioning
confidence: 65%
“…Specifically, it has been demonstrated that valence coding emerges with a slow latency (i.e., ~ 1 second) compared to stimulus onset. Population analyses with HMM confirmed this observation and provided further evidence indicating that, at a single trial level, valence coding emerges as a sudden and rapid change in the state of ensemble activity [31]. Recent ensemble recordings in rat GC showed that gapes (i.e.…”
Section: Introductionmentioning
confidence: 74%